Common genetic contributions to high-risk trauma exposure and self-injurious thoughts and behaviors. Issue 3 (6th May 2018) - Richmond-Rakerd, Leah S.; Trull, Timothy J.; Gizer, Ian R.; McLaughlin, Kristin; Scheiderer, Emily M.; Nelson, Elliot C.; Agrawal, Arpana; Lynskey, Michael T.; Madden, Pamela A.F.; Heath, Andrew C.; Statham, Dixie J.; Martin, Nicholas G.
Abstract: Background: Prior research has documented shared heritable contributions to non-suicidal self-injury (NSSI) and suicidal ideation (SI) as well as NSSI and suicide attempt (SA). In addition, trauma exposure has been implicated in risk for NSSI and suicide. Genetically informative studies are needed to determine common sources of liability to all three self-injurious thoughts and behaviors, and to clarify the nature of their associations with traumatic experiences. Methods: Multivariate biometric modeling was conducted using data from 9526 twins [59% female, mean age = 31.7 years (range 24–42)] from two cohorts of the Australian Twin Registry, some of whom also participated in the Childhood Trauma Study and the Nicotine Addiction Genetics Project. Results: The prevalences of high-risk trauma exposure (HRT), NSSI, SI, and SA were 24.4, 5.6, 27.1, and 4.6%, respectively. All phenotypes were moderately to highly correlated. Genetic influences on self-injurious thoughts and behaviors and HRT were significant and highly correlated among men [ r G = 0.59, 95% confidence interval (CI) (0.37–0.81)] and women [ r G = 0.56 (0.49–0.63)]. Unique environmental influences were modestly correlated in women [ r E = 0.23 (0.01–0.45)], suggesting that high-risk trauma may confer some direct risk for self-injurious thoughts and behaviors among females. Conclusions: Individuals engaging in NSSI are at increased risk for suicide, and common heritable factors contribute to these associations. Preventing trauma exposure may help to mitigate risk for self-harm and suicide, either directly or indirectly via reductions in liability to psychopathology more broadly. In addition, targeting pre-existing vulnerability factors could significantly reduce risk for life-threatening behaviors among those who have experienced trauma.